SIMA Austral: An operational information system for managing the Chilean aquaculture industry with international application. (20th November 2019) - Steven, Andrew D. L.; Aryal, Santosh; Bernal, Patricio; Bravo, Francisco; Bustamante, Rodrigo H.; Condie, Scott; Dambacher, Jeffrey M.; Dowideit, Sven; Fulton, Elizabeth A.; Gorton, Rebecca; Herzfeld, Mike; Hodge, Jonathan; et al.
ABSTRACT: The Integrated Management System for the Aquaculture (SIMA in Spanish) is a comprehensive interoperable information and modelling platform that has been developed to provide the Chilean Aquaculture industry and government agencies with access to improved environmental intelligence allowing them to make better informed strategic and operational decisions. SIMA is built upon an integrated system of biophysical production data, catchment and coastal-marine models, visualisation, reporting and risk-based decision support tools. This communication briefly describes the SIMA architecture and components and provides examples of applications of how it can be used to inform policy and management decisions, and discusses challenges and key learnings and considers future developments and applications.